2012
DOI: 10.1017/jmech.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Investigations of Low-Aspect-Ratio Thin Plate Wings at Low Reynolds Numbers

Abstract: To realize the relationship between flow structures of wingtip vortices and post stall characteristics of low aspect-ratio wings, this paper experimentally studies the aerodynamic characteristics and the corresponding flow structures of the rectangular thin-plate wings at Reynolds numbers between 10 4 and 10 5 . The aerodynamic properties to be studied include lift, drag, slopes at linear and nonlinear range of the lift curves and lift-to-drag ratios of the tested wings with the aspect ratio varying from 1.0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The pressure transducer was calibrated using a micro manometer and certified. The flow speed in the test section was then calculated using the incompressible steady Bernoulli's equation [19]. In the wind tunnel experiments, the area ratio is defined as A b /A w , where A b is the blade swept area and A w is the cross section area of the wind tunnel test section.…”
Section: Methodsmentioning
confidence: 99%
“…The pressure transducer was calibrated using a micro manometer and certified. The flow speed in the test section was then calculated using the incompressible steady Bernoulli's equation [19]. In the wind tunnel experiments, the area ratio is defined as A b /A w , where A b is the blade swept area and A w is the cross section area of the wind tunnel test section.…”
Section: Methodsmentioning
confidence: 99%
“…Gursul et al [1] used flow visualization technique to observe the vortex by providing smoke or dye to the flow field. In another study, Lambourne and Bryer [53] clarified the phenomenon over a slender delta wing with a sweep angle of Λ=65 o , in Figure 2.4. Erickson [24] also concluded that observations of the breakdown location in wind tunnel were in line with real flight observations.…”
Section: Vortex Breakdownmentioning
confidence: 93%
“…In particular, wing stall with accompanying bi-stable flow states (sometimes called hysteresis), triggered by bursting of the leading-edge separation bubble (LSB), should be avoided [6]. In contrast to airfoils and high-aspect-ratio wings, lift generation on low AR wings at high angles of attack is generated predominantly by wingtip vortices [7][8][9][10][11]. Although the majority of low AR investigations consider thin-plate-type wings [7][8][9][10][11], conventional wing profiles offer the critically important advantage of storage volume [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to airfoils and high-aspect-ratio wings, lift generation on low AR wings at high angles of attack is generated predominantly by wingtip vortices [7][8][9][10][11]. Although the majority of low AR investigations consider thin-plate-type wings [7][8][9][10][11], conventional wing profiles offer the critically important advantage of storage volume [12,13]. This has served as motivation to conduct basic research on conventional (non-flat-plate) profiles with rectangular planforms [14][15][16].…”
Section: Introductionmentioning
confidence: 99%